IV. STORAGE AND GERMINATION TESTS ON SHOREA JAVANICA SEEDS - UMBOH, M.I.J. (BIOTROPIA, 2024)
Seeds of Shorea javanica K & V (Dipterocarpaceae), were subjected to different treatments of temperature (27 ± 2°C, 20 ± 2°C and < 10°C), coating (ash and paraffin) and relative humidity (20, 66 and 86%) and their germination capability as well as moisture content assessed after 3, 7, 14 and 30 days of storage. The germination percentage of the seeds stored 30 days in a cloth bag under different conditions of temperature showed highly significant differences (a = 0.01). No significant differences were found on the effect of coating, duration of storage as well as on the interaction between these two factors. The moisture content of the seeds between 13 and 14% gave a germination percentage above 50% after 30 days.